Wear characteristics of medical hearing-aid components and friction reduction mechanisms - Song, Xu (2019)
The wear characteristics of a hearing-aid battery assembly, which consist of an acrylonitrile-butadiene-styren (ABS) button cell compartment and a stainless steel bracket with the locking knob, have been studied in the current work to predict its lifespan in service. The main failure mechanism is the worn-out of the cell compartment by the locking knob when changing the battery. Its wear rate is determined by the relationship between knob geometry and corresponding pressure distribution on the worn surface. Due to the third-body entrapment, the wear rate is highly influenced by the presence of the debris, and fortunately, it can be reduced by applying microsurface texture onto the knob. Experiments are conducted here to validate the wear reduction mechanism.